Investigation Of ZnO Nanostructures On Glass Substrate Deposited By Thermal Evaporation Method For UV Detection - Abed, Forat Hamzah (2018)
In this work, ZnO nanostructures with different morphologies were fabricated on a cost-effective glass substrate using a simple thermal evaporation in a conventional horizontal tube furnace via vapor–solid (VS) and vapor–liquid–solid (VLS) mechanisms. This study aims to provide a new approach for synthesis of one-dimensional (1D) and three-dimensional (3D) ZnO nanostructures using a low cost substrate by thermal evaporation of Zn powder in the presence of O2 gas, and determine optimal parameters to control high crystal quality and optical properties, thereby improving the performance of ultraviolet (UV) photodetectors (PDs) based on the produced ZnO.